2022
DOI: 10.3390/jcm11051187
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Periodontal Treatment Options and Their Impact on Subgingival Microbiota

Abstract: Background: Different periodontal treatment methods (quadrant-wise debridement, scaling and root planing (Q-SRP), full-mouth scaling (FMS), full-mouth disinfection (FMD), and FMD with adjuvant erythritol air-polishing (FMDAP)) were applied in periodontitis patients (stage III/IV). The study objective (substudy of ClinicalTrials.gov Identifier: NCT03509233) was to compare the impact of treatments on subgingival colonization. Methods: Forty patients were randomized to the treatment groups. Periodontal parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…These findings were similar to a previous research to some extent, indicating patients with periodontitis showed lower level of miR-1226 in GCF than healthy controls, and a negative correlation was found between miR-1226 expression, PPD, CAL, and BOP [18]. Nonsurgical periodontal treatments, including quadrant-wise debridement, scaling and root planning, full-mouth scaling, full-mouth disinfection (FMD), FMD with adjuvant erythritol air-polishing, and drug therapies were applied in periodontitis patients, with the purpose to improve both clinical and microbiologic outcomes [38,39]. With regard to the therapeutic implications exerted by clinical significance of miR-30b-3p and miR-125b-1-3p in periodontitis, as previously reported [40], tetramethylpyrazine is a promising agent and its anti-inflammatory and anti-apoptotic effects achieved by targeting miR-302b confer a protection to periodontal ligament stem cells from injuries induced by periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to a previous research to some extent, indicating patients with periodontitis showed lower level of miR-1226 in GCF than healthy controls, and a negative correlation was found between miR-1226 expression, PPD, CAL, and BOP [18]. Nonsurgical periodontal treatments, including quadrant-wise debridement, scaling and root planning, full-mouth scaling, full-mouth disinfection (FMD), FMD with adjuvant erythritol air-polishing, and drug therapies were applied in periodontitis patients, with the purpose to improve both clinical and microbiologic outcomes [38,39]. With regard to the therapeutic implications exerted by clinical significance of miR-30b-3p and miR-125b-1-3p in periodontitis, as previously reported [40], tetramethylpyrazine is a promising agent and its anti-inflammatory and anti-apoptotic effects achieved by targeting miR-302b confer a protection to periodontal ligament stem cells from injuries induced by periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The primary clinical therapies for periodontitis aimed at eliminating the plaque biofilm include mechanical scaling/root planing and surgical intervention. 8 However, irregular periodontal pockets, high technical sensitivity, and difficulty of operation have hindered these methods from achieving satisfactory results. 9 The systemic adjuvant administration of antibiotics can improve the effectiveness of mechanical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This includes hydroxide, methylmercaptan, dimethylsulfide, and other sulfur-containing compounds these compounds are produced by the Gram-negative and anaerobic bacteria that cause periodontal disease. 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%